Multi-Robot System Architecture Validation Using Disinfecting Robot Routine - Santos, Rafael Melo; Tavares, Carlos Joel; Ralha, Célia Ghedini (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2025)
Coordinating multiple robots to achieve shared goals across diverse scenarios remains a key challenge in Multi-Robot Systems (MRS). The literature proposes solutions where robots must collaborate, share information, and have planning recovery mechanisms to ensure mission continuity. The challenges involved are closely related to Multi-Agent Systems (MAS) integrated with Automated Planning (AP), often evaluated in limited and controlled scenarios. But to support claims of applicability, broader testing across diverse scenarios is essential. This work evaluates an MRS solution that integrates AP into an MAS, using a disinfecting robot routine as an illustrative study.